Interaction between innate immunity and porcine reproductive and respiratory syndrome virus - Sang, Yongming; Rowland, Raymond R. R.; Blecha, Frank (My University, 2011)
Innate immunity provides frontline antiviral protection and bridges adaptive immunity against virus infections. However, viruses can evade innate immune surveillance potentially causing chronic infections that may lead to pandemic diseases. Porcine reproductive and respiratory syndrome virus (PRRSV) is an example of an animal virus that has developed diverse mechanisms to evade porcine antiviral immune responses. Two decades after its discovery, PRRSV is still one of the most globally devastating viruses threatening the swine industry. In this review, we discuss the molecular and cellular composition of the mammalian innate antiviral immune system with emphasis on the porcine system. In particular, we focus on the interaction between PRRSV and porcine innate immunity at cellular and molecular levels. Strategies for targeting innate immune components and other host metabolic factors to induce ideal anti-PRRSV protection are also discussed.
Keywords: Innate antiviral immunity; PRRSV; Interferon; Vaccine